2004
DOI: 10.1530/eje.0.1510803
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II is present in pancreatic extracts and inhibits insulin release in the perfused rat pancreas

Abstract: Objective: Previous work from our laboratory has demonstrated that frog urotensin-II (UII), at a high concentration, inhibits glucose-induced insulin release in the rat pancreas. We have investigated the effect of rat UII and two structural analogs on insulin secretion and searched for the presence of UII-immunoreactivity in rat pancreatic extracts. Methods: The study was performed in the perfused rat pancreas. UII as well as its analogs were synthesized by solid phase methodology. Pancreatic extracts were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 51 publications
1
48
1
1
Order By: Relevance
“…6 Plasma U-II levels are known to be high in patients with diabetes mellitus. 8 Animal experiments have shown that U-II inhibits glucose-induced insulin release from pancreatic ␤-cells, 29 and stimulates hyperlipidemia by channeling glucose to free fatty acid synthesis. 30 These findings suggest that U-II may be associated with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Plasma U-II levels are known to be high in patients with diabetes mellitus. 8 Animal experiments have shown that U-II inhibits glucose-induced insulin release from pancreatic ␤-cells, 29 and stimulates hyperlipidemia by channeling glucose to free fatty acid synthesis. 30 These findings suggest that U-II may be associated with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…At high concentrations (100 nmol/l) frog UII inhibits glucose-and arginine-induced insulin responses in the rat pancreas (112). When synthetic rat UII was used on the same model, a dose-dependent inhibition of glucose-induced insulin release was observed once again (IC 50 ϭ 0.12 nmol/l) (111). This insulinostatic pathway of inhibition is independent of the somatostatin pathway (86).…”
Section: Pathological Significance Of Uiimentioning
confidence: 95%
“…In humans, single nucleotide polymorphism analysis in the Hong-Kong Chinese population confirmed that certain UTS2 gene haplotypes are associated with insulin resistance and pancreatic ␤-cell function (92). Thus, UII likely plays an important and direct inhibitory role on ␤-cell insulin secretion in an autocrine/paracrine manner, and may contribute to insulin resistance in pathological settings (111).…”
Section: Pathological Significance Of Uiimentioning
confidence: 97%
See 1 more Smart Citation
“…The UII gene is also expressed in the human and rat pancreas (Coulouarn et al, 1998;Ames et al, 1999;Sugo et al, 2003), and the evidence of the presence of the UII peptide has been found in a rat pancreas extract by reversed-phase HPLC analysis combined with radioimmunoassay detection (Silvestre et al, 2004), suggesting that UII may control pancreatic activity. The effect of UII on the endocrine pancreas has been studied using an in situ perfused rat pancreas model (Silvestre et al, 1986).…”
Section: E Effect Of Urotensin Ii/urotensin Ii-related Peptide On Thmentioning
confidence: 99%